Solar energy for liquid wastewater treatment with novel TiO2 supported catalysts - Martins, Rui C. (2022)
Photocatalytic oxidation is promising technology for removal of recalcitrant pollutants from water. Solar energy can be an interesting radiation source since the operating costs can be lower. However, the use of powder photocatalyst is a major drawback of the technology since suitable separation technologies are required and catalysts recovery is difficult. This work aims to test the suitability of using polymeric supports to immobilize TiO 2 in the reactor and apply it for parabens removal from water by solar photocatalytic oxidation. Polyurethanes (PU) and polydimethylsiloxane (PDMS) membranes were prepared and modified with TiO 2. While PU materials are only able to adsorb (35% in 1 h) parabens whichever the modification applied, modified PDMS was able to promote parabens photocatalytic oxidation removing 20% in 1 h under solar energy. Plasma/UV modification was able to active PDMS membranes (16% of methyl paraben (MP) removal) and further entrapment of TiO 2 in the polymeric matrix did not improve the process (18% of MP removal). Thus, only the superficial TiO 2 was active. Results show that PDMS is suitable material to support TiO 2 aiming photocatalytic wastewater treatment process using the Sun as a clean and renewable energy source.